Touch me carefully: a step towards understanding morphological diversity in the South American spiny sunflowers (Compositae, Barnadesioideae) - Ferreira, Paola De Lima; Antonelli, Alexandre; Groppo, Milton (Phytotaxa, 2021)
The subfamily Barnadesioideae (Compositae) is endemic to South America, comprising 10 genera and 80 species of mostly spiny herbs, subshrubs, shrubs, trees, or woody vines distributed from Venezuela to Argentina. Three genera, Dasyphyllum (27 species), Chuquiraga (22 spp.) and Barnadesia (19 spp.) contain 85% of the species, while the other seven genera (Archidasyphyllum, Arnaldoa, Doniophyton, Duseniella, Fulcaldea, Huarpea, and Schlechtendalia) are represented by up to three species each. Most species are found in xeric areas in the Andean and Patagonian regions—as in the Páramos, Puna and Patagonian steppe vegetation—with a secondary center of diversity in eastern South America. Previous phylogenetic hypotheses have clarified the relationships within the subfamily, showing that there are many non-monophyletic groups in different taxonomic ranks. As a result, taxonomic changes have been proposed over recent decades in order to reflect classifications comprising only monophyletic groups. In the present study, we provide a generic synopsis of the subfamily Barnadesioideae based on the most recent generic circumscriptions, including a key, expanded morphological descriptions, information on geographical distribution and habitat, photographs and taxonomic notes for all genera.